The state and the social : state formation in Botswana and Its Pre-Colonial and Colonial genealogies - Gulbrandsen, Ørnulf (Berghahn Books, 2012)
Botswana has been portrayed as a major case of exception in Africa--as an oasis of peace and harmony with an enduring parliamentary democracy, blessed with remarkable diamond-driven economic growth. Whereas the "failure" of other states on the continent is often attributed to the prevalence of Indigenous political ideas and structures, the author argues that Botswana's apparent success is not the result of Western ideas and practices of government having replaced Indigenous ideas and structures. Rather, the postcolonial state of Botswana is best understood as a unique, complex formation, one th.